2010
DOI: 10.1016/j.bpj.2009.12.1864
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Molecular Basis of the Assembly of the TRPP2/PKD1 Complex

Abstract: Mutations in PKD1 and TRPP2 account for nearly all cases of autoso-mal dominant polycystic kidney disease (ADPKD). These 2 proteins form a receptor/ion channel complex on the cell surface. Using a combination of biochemistry, crystallography, and a single-molecule method to determine the subunit composition of proteins in the plasma membrane of live cells, we find that this complex contains 3 TRPP2 and 1 PKD1. A newly identified coiled-coil domain in the C terminus of TRPP2 is critical for the formation of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
99
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(115 citation statements)
references
References 18 publications
13
99
2
1
Order By: Relevance
“…TRPP2 and PKD1 associate directly through their C termini (25,26), forming a complex containing three TRPP2 and one PKD1 (27). This association involves coiled-coil domains in the C termini of the two proteins (25,27).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…TRPP2 and PKD1 associate directly through their C termini (25,26), forming a complex containing three TRPP2 and one PKD1 (27). This association involves coiled-coil domains in the C termini of the two proteins (25,27).…”
mentioning
confidence: 99%
“…This association involves coiled-coil domains in the C termini of the two proteins (25,27). The TRPP2 coiled-coil domain forms a homotrimer, both in solution (27)(28)(29) and in crystals (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a functional PC2 trimeric channel has not been reported to present, recent studies are compatible with this hypothetical arrangement (9,22). These analyses, however, were performed with incomplete PC2ts.…”
Section: Discussionmentioning
confidence: 89%
“…Previous work has suggested that a coiled-coil subdomain identified in the PC2t (PC2t-CC) plays critical roles in PC2 oligomerization and in its physical interaction with PC1 to form the PC1-PC2 complex, a process that also involves a coiled-coil subdomain in PC1t (1). Another recent study, however, suggests that the PC2t-CC assembles as a homotrimer (9). A Ca þþ -binding EF-hand subdomain has also been predicted in PC2t and been proposed to function as a Ca þþ -sensing switch (2,10), whereas the PC2 channel activity has been shown to be regulated by calcium (4, 5, 11).…”
mentioning
confidence: 99%